2019
DOI: 10.1186/s42483-019-0023-9
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid homeostasis plays an important role in fungal development, fungicide resistance and virulence in Fusarium graminearum

Abstract: Phospholipids are major structural components of all cell membranes and participate in energy storage, signal transduction and environmental adaptability in eukaryotes. To date, the enzymes involved in phospholipid biosynthesis have been well characterized in budding yeast. However, their functions in filamentous fungi are largely unclear, especially their contribution to the interaction between phytopathogenic filamentous fungi and plants. In this study, we identified 10 phospholipid biosynthesis-related gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 60 publications
2
24
0
Order By: Relevance
“…Analysis of PL composition indicated that the main lipids in C. lunata IM 4417 biomass are PCs and PEs. This result is in accordance with published data, which show that the mentioned lipids account for over 50% of all PLs in fungi [ 32 , 33 ]. Both PC and PE are major structural lipids and determine membrane fluidity, wherein PCs are typical bilayer lipids and PEs are nonbilayer molecules.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Analysis of PL composition indicated that the main lipids in C. lunata IM 4417 biomass are PCs and PEs. This result is in accordance with published data, which show that the mentioned lipids account for over 50% of all PLs in fungi [ 32 , 33 ]. Both PC and PE are major structural lipids and determine membrane fluidity, wherein PCs are typical bilayer lipids and PEs are nonbilayer molecules.…”
Section: Discussionsupporting
confidence: 93%
“…On the basis of the presented results, it can be concluded that the addition of quinoline causes an increase in PC content and a decrease in PE amount. These PLs are crucial for vegetative fungal growth [ 33 ]. Thus, this change may be essential to maintaining the proper functioning of the cell in the presence of quinoline and can lead to increased membrane fluidity.…”
Section: Discussionmentioning
confidence: 99%
“…Choline metabolism is a critical function for both microbial and host physiology, as demonstrated by the increase seen in AGAu Candida species' related metabolites. Disruption of phospholipid biosynthesis in fungi can occur through inhibition of phosphatidylcholine synthesis, showing preventing virulence within the systemic mice model 87,88,120,121 . Further, acetylcholine is essential in the formation of the chitin wall characteristic of fungi 122,123 .…”
Section: Discussionmentioning
confidence: 99%
“…Protein secretion among the endoplasmic reticulum, Golgi, and vesicles involves classic membrane trafficking, and phospholipid synthesis takes place mainly in the endoplasmic reticulum, Golgi, endosomes, and vacuole. Phospholipids can be divided into phosphatidylinositol (PI), phosphatidylserine (PS), phosphatidylcholine (PC), and phosphatidylethanolamine (PE; Wang et al, 2019). To date, phospholipid biosynthetic genes have been well characterized in Saccharomyces cerevisiae.…”
Section: Introductionmentioning
confidence: 99%